Identifying Single Nucleotide Polymorphisms (SNPs) in OsFER1 and OsFER2 Genes Linked to Iron accumulation in Pigmented Indonesian Rice (Oryza sativa L.) - Pratiwi, Apriliana; Bassalamah, Rizka Fahma; Elvani, I Sabila; Sebastian, Alfino; Purwestri, Yekti Asih (Journal of Tropical Biodiversity and Biotechnology, 2024)
Iron (Fe) is an essential micronutrient for the well-being of plants, animals, and bacteria. In plants, iron plays a pivotal role in a myriad of metabolic processes, encompassing redox reaction, photosynthesis, respiration, chlorophyll synthesis, and nitrogen fixation. For humans, iron is indespensable for several metabolic functions, particularly in the synthesis of haemoglobin. Iron deficiency can lead to health issues on a global scale, therefore identifying key crops, such as rice for providing sufficient iron in diet intake is very important. In rice, the maintenance of iron homeostasis is orchestrated by various genes, with OsFER1 and OsFER2 acting as iron accumulator genes in leaves, stems, flowers, and grains. The primary objective of this study was to ascertain the single nucleotide polymorphisms (SNP) in the OsFER1 and OsFER2 and to assess the iron content in Indonesian local rice cultivars. To achieve this, we examined partial sequences of OsFER1 and OsFER2 to identify SNPs in the Indonesian rice cultivars used (Cempo Ireng, Pari Ireng, Hitam Kalsel, Merah Pari Eja, and Ciherang). Concurrently, the iron content in the seeds was quantified using Atomic Absorption Spectrophotometry (AAS). The analysis revealed that the OsFER1 gene sequence, specifically exon 5, exhibited a SNP in the form of a transition. In contrast, the OsFER2 gene sequences, specifically in intron 2 displayed SNPs in the form of insertions. Notably, the iron content in the seeds was highest in Cempo Ireng (black rice), while it was lowest in Merah Pari Eja (red rice) and Ciherang (non-pigmented rice). Importantly, the identified SNPs in these partial gene sequences did not exert any discernible influence on iron levels or the formation of ferritin protein.